Exact Solutions of the Conformable Space-Time Chiral Nonlinear Schrodinger’s Equations: Sekson Sirisubtawee, Nattawut Khansai, Sanoe Koonprasert, Montri Torvattanabun - Team, Support (Thai Journal of Mathematics, 2020)
In this paper, the modified simple equation method is used to obtain exact solutions of the space-time (1+1) and (2+1)-dimensional chiral nonlinear Schr ̈odinger’s equations in the sense of the conformable derivative. As a consequence, these obtained solutions with their constraint conditions can be useful to explain some physical phenomena such as dark or singular soliton solutions. Graphical representations of selected solutions are illustrated using a range of fractional orders. The performance of the method is concise, effective and reliable for solving nonlinear partial differential equations (NPDEs) including the NPDEs with conformable derivatives.